2019
DOI: 10.3390/f10060490
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Distribution of Ricania shantungensis (Hemiptera: Ricaniidae) in Korea: Application of Spatial Analysis to Select Relevant Environmental Variables for MaxEnt and CLIMEX Modeling

Abstract: Since the first report on its occurrence in 2010, Ricania shantungensis Chou & Lu in Korea has quickly spread. This pest population in agricultural areas has increased by over 100% each year and has caused serious economic damage in the last few years. This study was conducted to predict the potential habitat and the current and future distribution of R. shantungensis in Korea using CLIMEX and the Maximum Entropy Model (MaxEnt), and to suggest a new parameter selection method for both modeling programs. Weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…In comparison, variables pertaining to temperature or its variations were found to have significant influence on the predicted distributions of insect pest species in temperate regions, namely Dacus spp. [21] and Lobesia botrana [22] in China, Ricania shantungensis in Korea [24], Hylobius abietis and Cameraria ohridella in Europe [19], and six species of tephritid fruit flies in Europe [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, variables pertaining to temperature or its variations were found to have significant influence on the predicted distributions of insect pest species in temperate regions, namely Dacus spp. [21] and Lobesia botrana [22] in China, Ricania shantungensis in Korea [24], Hylobius abietis and Cameraria ohridella in Europe [19], and six species of tephritid fruit flies in Europe [20].…”
Section: Discussionmentioning
confidence: 99%
“…Particular species of insects have their own characteristic tolerance to climatic factors, and changes in such factors can lead to potential changes in distribution [17]. In view of this, Maxent modeling has been used to predict the current and potential distributions of invasive species [18], as well as those of a variety of forest and agricultural insect pests which include: the large pine weevil, Hylobius abietis L., and the horse-chestnut leaf miner, Cameraria ohridella Deschka and Dimič [19], and six tephritid fruit flies [20] in Europe; three species of tephritid flies under genus Dacus Fabricius [21] and the European grapevine moth, Lobesia botrana Denis and Schiffermüller, in China [22]; the ricaniid planthopper, Ricania shantungensis Chou and Lu in Korea [23,24]; the cotton mealybug, Phenacoccus solenopsis Tinsley, in India [25] and worldwide [26]; and the invasive European paper wasp, Polistes dominula Christ in the southern hemisphere [13].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the pitfall traps with attractants of pine twigs and ethanol are useful for monitoring and controlling H. abietis. Baek et al [29] evaluated the current and future distribution of Ricania shantungensis (Chou and Lu), which is an invasive planthopper and an important pest in agriculture and forestry in Korea [30], using CLIMEX and the Maximum Entropy Model (MaxEnt). In the MaxEnt, the most important variables determining the distribution of R. shantungensis were the annual mean temperature, mean temperature of the coldest month, maximum temperature in the warmest month, and precipitation of the driest month.…”
Section: Papers In This Issuementioning
confidence: 99%
“…List of papers included in the special issue. Pine twigs are better than artificial lures for trapping of pine weevils in pitfall traps Lalik et al [28] Insect Current and future distribution of Ricania shantungensis (Hemiptera: Ricaniidae) in Korea: Application of spatial analysis to select relevant environmental variables for MaxEnt and CLIMEX modelingBaek et al[29] Insect Occurrence prediction of the citrus Flatid planthopper (Metcalfa pruinosa (Say, 1830)) in South Korea using a random forest model Lee et al[31] …”
mentioning
confidence: 99%
“…Models produced using MaxEnt can be easily understood and interpreted and provide valuable insights on distribution and habitat suitability for a species [9,10]. MaxEnt modeling has been used to predict the current and potential distributions of invasive species [11], as well as those of a variety of forest and agricultural insect pests which include: the large pine weevil, Hylobius abietis L., and the horse-chestnut leaf miner, Cameraria ohridella Deschka and Dimič [12], and six tephritid fruit flies [13] [16,17]; and the cotton mealybug, Phenacoccus solenopsis Tinsley, in India [18] and worldwide [19] *Not covered by surveys in the current study. [20].…”
Section: Introductionmentioning
confidence: 99%